Morna, Identidade e Literatura em Cabo Verde - Brito, Geni Mendes de (2019)
Literature in Cape Verde experienced a significant development at the end of the 19th century, relying on the impulse of the newspapers that dynamized its fictional and poetic creation. However, it was in the twentieth century, with the emergence of the magazine Claridade (1936) that the Cape Verdean literary project was consolidated. In this magazine, the writers of the Archipelago try to focus, predominantly, on Creole themes, such as: the drama of droughts and their consequences, emigration and evasion, insularity and longing, recurrent themes told and sung through Morna- a musical genre, which assumes a privileged place in Cape Verdean literature and establishes a dialogue with the poetry, prose of fiction. Things that affects it and with which it interacts, constituting, thus, a diversified course in the literary Creole panorama. Knowing this importance, we propose in this research, to outline how poets and fictionists define, characterize and present Morna as the main theme of their work, or as one of the elements that grant the Cape Verdean identity to their texts, outlining their lyric, descriptive and dramatic narrative functions. In order to write the present work "Morna, Identity and Literature in Cape Verde" - our methodological proposal focuses on a documentary and bibliographic research, based on literary, historical and anthropological sources. The theoretical-critical basis was developed from the studies of Juliana Brás Dias, Benilde Justo Caniato, Manuel Ferreira, Moacyr Rodrigues, Simone Caputo Gomes, Vasco Martins, Gabriel Mariano, among others. We found out that among various musical genres present in Cape Verde, Morna is undoubtedly the most cultivated musical and poetic form in all the islands of the archipelago. It symbolizes Cape Verdean sentiment of sadness, anguish and pain, which, even under the weight of colonial and cultural domination, resists and manifests itself, mainly through the language (the Creole), a major symbol that unifies the Cape Verdean universe .